Upper tropospheric cyclonic vortex and brazilian northeast jet stream over alagoas state: Circulation patterns and rainfall - Repinaldo, Henrique Fuchs Bueno [UNESP]; Fedorova, Natalia; Levit, Valdimir; da Rocha Repinaldo, Cintia Rabelo (FapUNIFESP (SciELO), 2020)
Interaction between Brazilian Northeast Jet Stream (BNEJS) and Upper Tropospheric Cyclonic Vortexes (UTCV) isn’t still well known, as well as its seasonal variability and relation with rainfall pattern. This study’s aim is to determine the air circulation patterns in UTCV events with BNEJS in La Niña and El Niño years and its connections with rainfall in the Alagoas State. These connections were analyzed for 9 years between 1988 and 2000 in El Niño, La Niña and Neutral years. NCEP Reanalysis data, rainfall data from 71 meteorological stations and satellite images were used. Fifty-eight percent of 140 observed UTCVs were associated with BNEJS events located in the Brazilian Northeast and 26%, loca- ted over the Alagoas State. Three types of BNEJS patterns, denominated as Meridional (M), Zonal (Z) and Transversal (T), have been identified. The M-type BNEJS was the most frequent in Alagoas State, especially in El Niño years. Z and T-types occurred less frequently and were rarely seen in La Niña years. The results showed that in the M-type BNEJS events in 48% of days were not registered precipitation, while Z and T events recorded rainfall in almost 96% of the days.
Vórtice ciclônico em altos níveis e corrente de jato do nordeste brasileiro sobre o estado de alagoas: Padrões de circulação e precipitação
Keywords: Brazilian northeast jet stream; ENSO; Upper tropospheric cyclonic vortexes